2012
DOI: 10.1523/jneurosci.2050-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of the Human Glycine Receptor Revealed by Direct Subunit Counting

Abstract: The subunit stoichiometry of heteromeric glycine-gated channels (GlyRs) determines fundamental properties of these key inhibitory neurotransmitter receptors; however the ratio of α1 to β-subunits per receptor remains controversial. We used single molecule imaging and stepwise photobleaching in Xenopus oocytes to directly determine the subunit stoichiometry of a glycine receptor to be 3α1:2β. This approach allowed us to determine the receptor stoichiometry in mixed populations consisting of both heteromeric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 37 publications
8
106
0
5
Order By: Relevance
“…S1 and S2). This probability value of mEGFP being fluorescent is similar to what was observed previously for mEGFP fused to a number of other membrane proteins (28)(29)(30)(31)(32)(33). Binomial predictions based on four subunits also accounted well for the other hBest family members ( Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…S1 and S2). This probability value of mEGFP being fluorescent is similar to what was observed previously for mEGFP fused to a number of other membrane proteins (28)(29)(30)(31)(32)(33). Binomial predictions based on four subunits also accounted well for the other hBest family members ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…Although earlier biochemical studies concluded that the Best1 channel is an oligomer, the estimate of the number of subunits ranged from 2 to 5 (22,27). To resolve this question, we used the single-molecule subunitcounting method (28)(29)(30)(31)(32)(33) to determine the number of subunits by counting the number of fluorescence-bleaching steps of monomeric enhanced green fluorescent protein (mEGFP)-tagged hBest1 in Xenopus oocytes [EGFP-tagged hBest1 was previously shown to be functional (34)]. The main advantages of this method are that: (i) the counting uses Total Internal Reflection Fluorescence Microscopy (TIRFM) to focus exclusively on functional channels in their native physiological environment, the plasma membrane of live cells, and (ii) because the level of expression can be easily controlled in oocytes, it is possible to obtain low enough densities so that each channel appears as an individual fluorescent spot that can be readily resolved from its neighbors.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in previous studies, blinking of PAFPs can be corrected by combining fluorescent bursts from a single molecule based on a cutoff time determined from the measured characteristic darktime distribution (25,27). In addition, it has been previously reported that the detectable fraction of PAFPs can be substantially smaller than 100% (29)(30)(31). Both the blink characteristics and the detectable fraction are sensitive to the experimental conditions.…”
Section: Calibration Of Single-molecule Superresolution Microscopy Elmentioning
confidence: 85%
“…Ϫ26Ј -␣1 19Ј coupling energy implies the presence of at least one ␣1-␣1 interface. The stoichiometry of ␣1␤ GlyRs is in dispute, with some studies finding evidence for a 3␣:2␤ ratio (42,43) and others for a 2␣:3␤ ratio (26,27). If ␣ and ␤ subunits alternate in the pentamer, as proposed by both the Grudzinska and Yang studies (26,27), the presence of at least one ␣1-␣1 interface necessitates a 3␣:2␤ ratio.…”
Section: Discussionmentioning
confidence: 99%